Nucleus–Invadopodia Duo During Cancer Invasion. Issue 2 (February 2019) - Ferrari, Robin; Infante, Elvira; Chavrier, Philippe
Abstract : Matrix proteolysis mediated by MT1-MMP facilitates the invasive migration of tumor cells in dense tissues, which otherwise get trapped in the matrix because of limited nuclear deformability. A digest-on-demand response has been identified, which requires nucleus–microtubule linkage through the LINC complex and triggers MT1-MMP surface-exposure to facilitate nucleus movement.